LncRNA, an Emerging Approach for Neurological Diseases Treatment by Regulating Microglia Polarization - Gao, Xiaoyu; Cao, Zilong; Tan, Haifeng; Li, Peiling; Su, Wenen; Wan, Teng; Guo, Weiming (Frontiers in Neuroscience, 2022)
Neurological disorders cause untold human disability and death each year. For most neurological disorders, the efficacy of their primary treatment strategies remains suboptimal. Microglia are associated with the development and progression of multiple neurological disorders. Targeting the regulation of microglia polarization has emerged as an important therapeutic strategy for neurological disorders. Their M1/M2 type microglia are closely associated with neuronal apoptosis, synaptic plasticity, blood-brain barrier integrity, resistance to iron death, and astrocyte regulation. lncRNA, a recently extensively studied non-coding transcript of over 200 nucleotides, has shown great value to intervene in microglia polarization. It can often participate in gene regulation of microglia by directly regulating transcription or sponging downstream miRNAs, for example. Through proper regulation, microglia can exert neuroprotective effects, reduce neurological damage and improve the prognosis of many neurological diseases. This paper reviews the progress of research linking lncRNAs to microglia polarization and neurological diseases.